Influences of SLF electromagnetic fields in current carrier conductors - (:unkn) unknown (IEEE, 2003)
In this paper, the electromagnetic fields emitted from power cables in the high buildings and houses are investigated. This paper includes the analysis of electromagnetic fields generated by the three phase conductors at a point. For this aim, a laboratory model was designed, and then SLF electromagnetic field values were measured in air and inside model wall. Finally the measured values were compared with the calculated values, which are determined using PC simulation software. The measured values are close to the calculated values. The lab model is a 2.3 in height metal plate. Various electromagnetic field measurements were performed starting from 0.1 in to 3 in in order in different cable separations. In addition, effect of the different sizes PC monitors located in front of the cables was investigated. Keyword: Electromagnetic Field, Raiser Cable, Power Cable, Carrier Conductor, Influence, Effect on Human and PC.
Keywords: electromagnetic field; raiser cable; power cable; carrier conductor; influence; effect on human and PC